Livelihood Strategy Based On Assets As Efforts To Establish Scavenger Empowerment In Facing The Poverty Of Living In The City: (Case Study of Scavengers at Njawar, Surabaya) - Mahendrawati, Ita Kusuma; Prasetijowati, Tri (Advances in Social Sciences Research Journal, 2020)
Surabaya as the second largest city in Indonesia has its large scale Final Disposal Site (FDS) in Njawar. There are quite a lot of scavengers in this area. They live in a village not far from the landfill site - FDS. Unfortunately, the Surabaya city government has already extended the waste management to the private sector leading to an impact on the income of the scavengers there. On the other hand, the human resources are very minimal. In responding such a situation, the scavengers apply the livelihood strategy to empower themselves to survive amid the urban poverty. This study aims to determine the livelihood strategy undertaken by the scavengers in building their empowerment in Surabaya landfill and some factors affecting it. The livelihood strategy consists of acquisition, allocation and social networking. Also the community applies the livelihood strategy for the assets owned comprising of physical, financial, social, waste, and spiritual assets, In addition, the results of research indicated that work ethic, work motivation, the role of the collectors as mediators, facilitators and patrons have a significant influence on the livelihood strategies undertaken by the scavengers . The job as a scavenger can be classified as a profession although this type of profession has not been recognized by the state. Such a condition like this leads to less government participation in the scavenging community. The result of the study recommended the involvement of the related agencies such as Social Service, Office of Sanitation and Gardening, NGOs and Universities to issue a policy to regulate all the necessary things in finding out the matters of the scavengers. The participation of the governments of the native cities of the scavengers is highly expected. Some employments are supposed to be provided by their hometown so as to reduce the flow of urbanization